Neuroleptic malignant syndrome in a patient with moderate intellectual disability treated with olanzapine: A case report - Francesco Piacenza; Suet Kee Ong; Patrick O’Brien; Maurice Clancy (Clinical Case Reports, 2021)
Abstract This case demonstrates the challenges encountered in a case of Neuroleptic Malignant Syndrome in a young woman with moderate Intellectual Disability.